1995
DOI: 10.1002/aja.1002040106
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pattern of expression of the mouse α1(XI) collagen gene (Col11a1)

Abstract: Fibrillar networks are intimately involved in several morphogenetic processes which underlie the harmonious development of the vertebrate embryo. Recent genetic evidence has demonstrated that the minor types V and XI collagen are key regulators of types I and XI fibrillogenesis in non-cartilaginous and cartilaginous matrices, respectively. A comprehensive understanding of the expression and regulation of the genes coding for the chains of the minor collagen types is therefore relevant to animal morphogenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 35 publications
1
42
1
2
Order By: Relevance
“…We demonstrated that CBF/NF-Y bound to the Ϫ147 to Ϫ121 region but could not find any protein-DNA complex in the Ϫ199 to ϩ271 region. These data are not consistent with the previous experiments using DNA footprinting techniques, in which three areas, FP1 (Ϫ63 to Ϫ51), FP2 (Ϫ111 to Ϫ95), and FP3 (Ϫ171 to Ϫ159), were protected using the nuclear extracts from a primary line of smooth muscle cells, called 1120 (14). We do not know the reason for this discrepancy so far.…”
Section: Figcontrasting
confidence: 92%
“…We demonstrated that CBF/NF-Y bound to the Ϫ147 to Ϫ121 region but could not find any protein-DNA complex in the Ϫ199 to ϩ271 region. These data are not consistent with the previous experiments using DNA footprinting techniques, in which three areas, FP1 (Ϫ63 to Ϫ51), FP2 (Ϫ111 to Ϫ95), and FP3 (Ϫ171 to Ϫ159), were protected using the nuclear extracts from a primary line of smooth muscle cells, called 1120 (14). We do not know the reason for this discrepancy so far.…”
Section: Figcontrasting
confidence: 92%
“…Sheet-embedded cells also expressed genes encoding for components of the embryonic cardiac extracellular matrix (laminin, collagens I, XI, and XVIII) [29][30][31]. These findings indicate that, in some respect, a three-dimensional engineered tissue could mimic the natural environment allowing progenitor cells embedded in a proper extracellular matrix to stably display a very lowrate division and apoptosis [23].…”
Section: Discussionmentioning
confidence: 85%
“…In the developing mouse, the gene was expressed in the vertebrae, in the osteoblasts of the trabecular bone and in the chondroid tissue of the intervertebral disc (Yoshioka et al, 1995). In salmon it was found in the osteoblast of the trabecular and compact bone, even though expression was much higher in notochordal chordoblasts (Fig.…”
Section: A Wargelius and Othersmentioning
confidence: 99%